Poland : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
This report provides the details of the IMF's projections and estimates on the Republic of Poland's sectoral breakdown of investment; value added by sector; growth and structure of agricultural production, during 1992-98; wages and salaries; private sector employment by sector, during 1993-98; monetary survey; balance sheet of the national bank of Poland, during 1993-99; consolidated general government operations; state budget revenue and expenditure; operations of main extrabudgetary funds; state debt stock, during 1992-99; interest rates,1995-99; price developments, 1990-99, and so on.